Fictive motion in modern Persian within the framework of cognitive semantics - Nikabadi, Masha; Lotfi, Ahmadreza; Hadian, Bahram (Penerbit Universiti Kebangsaan Malaysia, 2024)
This paper tries to implement Talmy's (2000) model of fictive motion in the Persian language to investigate incipiently to what extent this model of fictive motion events is applicable in the Persian language and secondarily to inspect the semantic constituents of fictive motion sentences. Therefore, a preference task entailing sixteen extracted sentences from Talmy's (2000) classifications of fictive motion was developed to scrutinise Persian speakers' intuitions in evaluating fictive motion. These sentences were translated into Persian, and a similar sentence was also reproduced for every translated sentence, as well as nine pairs of filler sentences, to analyse the cognitive quality of fictive motion events perceived by the Persian speakers. One hundred and five Persian students participated in a two-stage task based on a convenience sampling procedure. The results reported that 86.9% of participants marked motion sentences. Since prepositional phrases were singled out, with an average of 56, as the motion constituents, it leads to the conclusion that Paths are the most frequent semantic elements in the Persian language.